INTEGRASI DATA KARYA ILMIAH PADA WEBSITE WIDURI.RAHARJA.INFO KE DALAM WEBSITE RAHARJA.AC.ID - Ary Budi Warsito; Indri Handayani; Nuzulia Eka Putri (CCIT Journal, 2015)
Media information through the Internet is growing rapidly and incessantly. This is one manifestation of the development of information systems technology is so rapid. An information transmitted between a database with another database that allows to interact in a distributed database system. In Raharja College, students are trained to produce scientific work such as paper, the report KKP/TA / SKRIPSI. Widuri is the place of manufacture and storage of the report KKP/TA / SKRIPSI College Prog. This is one manifestation of the development of information systems technology is so rapid that affect the world of education. College Prog has an official website that raharja.ac.id as a variety of information in colleges raharja to optimize the website raharja acid in her integration into the data on the website widuri acid raharja website in order to facilitate students in accessing scientific papers reporting data